MEMBANGUN WEBSITE PROFILE KELURAHAN MELAYU TENGGARONG - Yulindawati Yulindawati; Hanifah Ekawati (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2020)
The research to build Website Profile of Tenggarong Kelurahan is a study to facilitate the public to obtain complete and up-to-date information because the information is felt to be very important in decision making and in achieving goals. In addition to obtaining complete and up-to-date information, the website can also send and publish information to the wider community online. The system development method used in this research is the System Development Life Cycle (SDLC) method, or better known as the system development life cycle in system engineering and software engineering, is the process of making and changing systems and the models and methodologies used to develop these systems. The long-term goal to be achieved is that it is hoped that this system will be able to publicize its activities for more up-to-date information so that the public can find out about the activities that have been carried out, ease of information on the procedures for handling correspondence in the Melayu Tenggarong village to the public at large. So that the specific target of using the Tenggarong Kelurahan website as an effective medium for delivering information can be achieved.